The sterling area – part I - WIGHTMAN, D. (PSL Quarterly Review, 2014)
The article outlines the origins and the developments of the sterling area from the beginning of the last century to the eve of World War II. The author stresses the crucial events and the successive stages which transformed a mere set of commercial and financial connexions in a currency system in the nineteen thirties. “The pressing needs of war made it necessary to give the system statutory definition and subject it to a systemic regulation.” JEL: E42